Auraptene in the Peels of Citrus kawachiensis (Kawachi Bankan) Ameliorates Lipopolysaccharide-Induced Inflammation in the Mouse Brain - Okuyama, Satoshi (Hindawi Publishing Corporation, 2014)
Examination of the dried peel powder of Citrus kawachiensis, one of the citrus products of Ehime, Japan, showed that it contained naringin (NGIN; 44.02 ± 0.491 mg/g), narirutin (NRTN; 4.46 ± 0.0563 mg/g), auraptene (AUR; 4.07 ± 0.033 mg/g), and 3,5,6,7,8,3′,4′-heptamethoxyflavone (HMF; 0.27 ± 0.0039 mg/g). When this dried peel powder was orally preadministered at the dose of 1.2 or 2.4 g/kg/day for 7 days into lipopolysaccharide- (LPS-) injected mice, an animal model of systemic inflammation, it suppressed (1) LPS-induced loss of body weight and abnormal behavior in the open field, (2) LPS-induced activation of microglia and astrocytes in the hippocampus, and (3) LPS-induced expression of cyclooxygenase (COX)-2, which were coexpressed in astrocytes of these mice. When NGIN or AUR was preadministered to LPS-injected mice at an amount similar to that in the peel powder, AUR, but not NGIN, had the ability to suppress the LPS-induced inflammation in the brain of these model mice. The dried powder of flavedo tissue (the outer colored layer of the mesocarp of a citrus fruit) and juice, which contained sufficient amounts of AUR, also had anti-inflammatory effect. These results suggest that AUR was the main ingredient responsible for the anti-inflammatory property of the dried peels of C. kawachiensis.